Hyperplastic callus formation in congenital insensitivity to pain: A masquerader of osteosarcoma - Maha Anwar; Maha Rashid Malik; Shaarif Bashir; Usman Hassan; Alina Sadaf (Pediatric Hematology Oncology Journal, 2023)
Background: Congenital insensitivity to pain (CIP) is a rare genetic disorder characterized by the inability to experience pain. Unrecognized, repeated injuries may result in poorly healed fractures with hyperplastic callus formation, auto-amputation of digits, and osteomyelitis. In addition, the loss of joint proprioception leads to neuropathic osteoarthropathy (Charcot joints). Case report: A child with a progressively increasing swelling of the left proximal tibia and an aggressive bone lesion on imaging was suspected to have osteosarcoma. The diagnosis of hyperplastic callus formation was established through a multidisciplinary approach with imaging and repeat tissue biopsy. Conclusion: In the context of CIP, malignant bone tumors, including osteosarcoma are a differential diagnosis and require a review of history, examination, radiology and histology.